PENGARUH OROPHARYNGEAL KOLOSTRUM TERHADAP GEJALA INFEKSI PADA BAYI PREMATUR DI RUANG NEONATAL INTENSIVE CARE UNIT - Hanum, Farida; Simanjuntak, Samuel Maju; Nurjanah, Nunung (Jurnal Ilmiah Keperawatan IMELDA, 2024)
The problem of prematurity continues to be a concern in today's modern era. Preterm birth is a major cause of neonatal morbidity and mortality. One of the efforts to prevent infection in preterm infants is by giving oropharyngeal colostrum to preterm infants. Objective: to analyze the effect of oropharyngeal colostrum on symptoms of infections in preterm infants in the NICU Room of Ummi Hospital Bogor. Method: the type of research used in this study was a pre-experimental design with one group pre-post test design. non-probability sampling technique with purposive sampling. The measuring instrument used was the form Newborn-Assessment-Observation-Chart and Early Warning Score with Mc Nemar analysis. The number of respondents was 26 premature infants. Results: the characteristics of respondents aged one-day premature babies 22 respondents (88.5%). Birth weight ? 1,500 gr 15 respondents (57.7%), and 53.8% were female. Symptoms of suspected infection during the pre-test were 16 respondents (61.5%) and the uninfected category amounted to 10 respondents (38.5%). At the same time, the post-test obtained symptoms of non-infection of 16 respondents (61.5%) and suspected infection of 10 respondents (38.5%). Conclusion: This study obtained p = 0.07 which showed no effect of oropharyngeal colostrum administration on the incidence of infection in premature infants in the NICU room of Ummi Bogor Hospital.